Assessing impacts of alternative fertilizer management practices on both nitrogen loading and greenhouse gas emissions in rice cultivation. (October 2015) - Zhao, Zheng; Yue, Yubo; Sha, Zhimin; Li, Changsheng; Deng, Jia; Zhang, Hanlin; Gao, Maofang; Cao, Linkui
Abstract: Nitrogen (N) losses and greenhouse gas (GHG) emissions from paddy rice fields contaminate water bodies and atmospheric environment. A 2-year (2012–2013) field experiment was conducted at a typical paddy rice field in a rural suburb of Shanghai, China. N losses and GHG emissions from the paddy field with alternative fertilizer management practices were simultaneously measured. Four treatments were tested in the experiment: applications of only chemical synthetic fertilizer urea (CT), only organic manure (OT), a combination of the two types of fertilizers (MT) and a control (CK). Results from the field study indicated that CT produced the highest seasonal N loading rate (18.79 kg N/ha) and N2 O emissions (1.81 kg N2 O/ha) but with the lowest seasonal CH4 emissions (69.09 kg CH4 /ha). With organic manure applied, MT and OT respectively reduced N loading by 21.86% and 30.41%, reduced N2 O emissions by 28.34% and 69.41%, but increased CH4 emissions by 137% and 310% in comparison with CT. However, the net impact of CH4 and N2 O emissions on global warming was enhanced when organic manure was applied. In addition, CT and MT produced the optimal rice yield during the experimental period, while OT treatment led to a yield reduction by 9.29% compared with CT. In conclusion, the impacts of alternative fertilizer management practices on ecosystem services ought to be assessed specifically due to the great variations across rice yields, N loss and GHG emissions. Highlights: N loss and GHG emissions were measured from a paddy field in Shanghai. N loss associated to different precipitation patterns. GHG emissions related to different fertilizer and water management. Application of urea increased N losses and N2 O emissions. Application of organic manure enhanced CH4 emissions and net GWP.